Development of Genetic Tools for the Manipulation of the Planctomycetes - Rivas-Marín, Elena; Canosa, Inés; Santero, Eduardo; Devos, Damien P. (Frontiers in Microbiology, 2016)
Bacteria belonging to the Planctomycetes, Verrucomicrobia, Chlamydiae (PVC) superphylum are of interest for biotechnology, evolutionary cell biology, ecology and human health. Some PVC species lack a number of typical bacterial features while others possess characteristics that are usually more associated to eukaryotes or archaea. For example, the Planctomycetes phylum is atypical for the absence of the FtsZ protein and for the presence of a developed endomembrane system. Studies of the cellular and molecular biology of these infrequent characteristics are currently limited due to the lack of genetic tools for most of the species. So far, genetic manipulation in Planctomycetes has been described in Planctopirus limnophila only. Here we show a simple approach that allows mutagenesis by homologous recombination in three different planctomycetes species (i.e. Gemmata obscuriglobus, Gimesia maris and Blastopirellula marina), in addition to P. limnophila, thus extending the repertoire of genetically modifiable organisms in this superphylum. Although the Planctomycetes show high resistance to most antibiotics, we have used kanamycin resistance genes in G. obscuriglobus, P. limnophila and G. maris, and tetracycline resistance genes in B. marina, as markers for mutant selection. In all cases, plasmids were introduced in the strains by mating or electroporation, and the genetic modification was verified by Southern Blotting analysis. In addition we show that the green fluorescent protein (gfp) is expressed in all four backgrounds from an Escherichia coli promoter. The genetic manipulation achievement in four phylogenetically diverse planctomycetes will enable molecular studies in these strains, and opens the door to developing genetic approaches not only in other planctomycetes but also other species of the superphylum, such as the Lentisphaerae.